What Works and Why: Insights from Science Teachers’ In-Service Capacity Development Programme - Patra, Tamralipta (Voices of Teachers and Teacher Educators, 2024)
Science, as a discipline, holds immense significance to understand this world. This subject encompasses and enhances one’s ability to think critically, observe, infer, solve problems, experiment, and analyse complex phenomena. Given the importance of this subject, effective science teaching is imperative. However, science teachers in the public school system face numerous challenges like high class strength, shortages of teachers, non-academic engagements, inadequate infrastructure, and limited resources. This paper outlines the status of science teaching in public schools, shedding light on some of the issues that impede the teaching–learning process. It also discusses the significance of in-service capacity enhancement programmes for science teachers. Additionally, the paper recognises and describes effective strategies employed in in-service capacity enhancement workshops.